Hazard perception skills of young drivers with Attention Deficit Hyperactivity Disorder (ADHD) can be improved with computer based driver training: An exploratory randomised controlled trial - Bruce, C.; Unsworth, C.; Dillon, M.; Tay, R.; Falkmer, Torbjorn; Bird, P.; Carey, L. (Elsevier Ltd, 2017)
Â© 2017 Elsevier Ltd Background: Young drivers with Attention Deficit Hyperactivity Disorder (ADHD) are at higher risk of road traffic injuries than their peers. Increased risk correlates with poor hazard perception skill. Few studies have investigated hazard perception training using computer technology with this group of drivers. Objectives: *Determine the presence and magnitude of the between-group and within- subject change in hazard perception skills in young drivers with ADHD who receive Drive Smart training. *Determine whether training-facilitated change in hazard perception is maintained over time. Methods: This was a feasibility study, randomised control trial conducted in Australia. The design included a delayed treatment for the control group. Twenty-five drivers with a diagnosis of ADHD were randomised to the Immediate Intervention or Delayed Intervention group.The Immediate Intervention group received a training session using a computer application entitled Drive Smart. The Delayed Intervention group watched a documentary video initially (control condition), followed by the Drive Smart computer training session. The participant's hazard perception skill was measured using the Hazard Perception Test (HPT). Findings: After adjusting for baseline scores, there was a significant betweengroup difference in post-intervention HPT change scores in favour of the Immediate Intervention group. The magnitude of the effect was large. There was no significant within-group delayed intervention effect. A significant maintenance effect was found at 6-week follow-up for the Immediate Intervention group. Conclusions: The hazard perception skills of participants improved following training with large effect size and some maintenance of gain. A multimodal approach to training is indicated to facilitate maintenance. A full-scale trial is feasible.